Exploring the role of learning in sustainability transitions: a case study using a novel analytical approach. Issue 3 (3rd December 2020) - Plummer, Paul; Van Poeck, Katrien
Abstract: Based on an exploratory case study of a community food waste initiative in Gothenburg, Sweden, this article presents a novel analytical approach to studying the role of learning within sustainability transition niches. The article's theoretical perspective draws from pragmatist educational philosophy, practice theory, and sustainability transition studies. Proceeding from this theoretical perspective, a two-stage empirical analysis is conducted using dramaturgical analysis and practical epistemology analysis, methods from sociology and the educational sciences. Building on this analysis, the article introduces the concept of educative practices, through which it is argued that a role of learning at the niche level within sustainability transitions is to interrupt the reproduction of norms and attitudes within socio-technical systems. The article thus offers original analytical and conceptual tools for investigating sustainability transitions in relation to learning.